1
1
mirror of https://github.com/thma/WhyHaskellMatters.git synced 2024-09-11 13:46:11 +03:00

add functor proof

This commit is contained in:
Mahler, Thomas 2020-04-16 12:41:05 +02:00
parent 8a257be84c
commit 870cb687fb
2 changed files with 84 additions and 0 deletions

View File

@ -1575,6 +1575,7 @@ value with an output value, and does nothing else. In particular,
Purity makes it easy to reason about code, as it is so close to mathematical calculus.
The properties of a Haskell program can thus often be determined with equational reasoning.
(As an example I have provided an [example for equational reasoning in Haskell](functor-proof.md).
Purity also improves testability: It is much easier to set up tests without worrying about mocks or stubs to factor out
access to backend layers.

83
functor-proof.md Normal file
View File

@ -0,0 +1,83 @@
# Proof of functor laws for Maybe
**Facts:**
This is the `Functor` instance declaration of the type `Maybe`:
```haskell
instance Functor Maybe where
fmap _ Nothing = Nothing -- (1)
fmap f (Just a) = Just (f a) -- (2)
```
This is the declaration of the composition operator `(.)`:
```haskell
(.) :: (b -> c) -> (a -> b) -> a -> c
f . g x = f (g x) -- (3)
```
This is the definition of the Identity function `id`:
```haskell
id :: a -> a
id x = x -- (4)
```
Now we are asked to proof that `Maybe` fulfils the functor laws:
```haskell
1.: fmap id = id
2.: fmap (f . g) = (fmap f . fmap g)
```
## Proof of the first law
**Claim:** `fmap id m = id m`, for any `m` of type `Maybe a`.
**Proof.** On cases of `m`.
*Case 1:* `m = Nothing`.
```haskell
fmap id m = fmap id Nothing -- by expansion of m
= Nothing -- by applying equation (1)
= id m -- by definition m, by applying equation (4)
```
*Case 2:* `m = Just a`.
```haskell
fmap id m = fmap id (Just a) -- by expansion of m
= Just (id a) -- by applying equation (2)
= Just a -- by expansion of id (equation (4))
= m -- by definition of m
= id m -- by applying equation (4)
```
Therefore, `fmap id m = id m` in all cases.∎
## Proof of the second law
**Claim:** `fmap (f . g) m = (fmap f . fmap g) m`, for any `m` of type `Maybe a`.
**Proof.** On cases of `m`.
*Case 1:* `m = Nothing`.
```haskell
fmap (f . g) m = fmap (f . g) Nothing -- by expansion of m
= Nothing -- by applying equation (1)
(fmap f . fmap g) m = fmap f (fmap g Nothing) -- by expansion of (.) and m
= fmap f Nothing -- by applying equation (1)
= Nothing -- by applying equation (1)
```
*Case 2:* `m = Just a`.
```haskell
fmap (f . g) m = fmap (f . g) (Just a) -- by expansion of m
= Just ((f . g) a) -- by applying equation (2)
(fmap f . fmap g) m = fmap f (fmap g (Just a)) -- by expansion of (.), m
= fmap f (Just (g a)) -- by applying equation (2)
= Just (f (g a) -- by applying equation (2)
= Just ((f . g) a) -- by applying equation (3)
```
Therefore, `fmap (f . g) m = (fmap f . fmap g) m` in all cases. ∎